2020
DOI: 10.1523/jneurosci.0288-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Induction of BDNF Expression in Layer II/III and Layer V Neurons of the Motor Cortex Is Essential for Motor Learning

Abstract: Motor learning depends on synaptic plasticity between corticostriatal projections and striatal medium spiny neurons. Retrograde tracing from the dorsolateral striatum reveals that both layer II/III and layer V neurons in the motor cortex express Brain-derived neurotrophic factor (BDNF) as a potential regulator of plasticity in corticostriatal projections in male and female mice. The number of these BDNF expressing cortical neurons and levels of BDNF protein are highest in juvenile mice when adult motor pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 100 publications
(210 reference statements)
2
30
0
Order By: Relevance
“…We also found that a subset of BDNF-positive neurons in the motor cortex and the mPFC extends projections to the DLS. The motor cortex is known for innervating the DLS (Yin and Knowlton, 2006) and Andreska et al recently reported that BDNF in this corticostriatal circuit is essential for motor learning (Andreska et al, 2020). We show herein that OFC BDNF neurons project to the dorsal striatum.…”
Section: Characterization Of Corticostriatal Bdnf Neuronssupporting
confidence: 58%
See 1 more Smart Citation
“…We also found that a subset of BDNF-positive neurons in the motor cortex and the mPFC extends projections to the DLS. The motor cortex is known for innervating the DLS (Yin and Knowlton, 2006) and Andreska et al recently reported that BDNF in this corticostriatal circuit is essential for motor learning (Andreska et al, 2020). We show herein that OFC BDNF neurons project to the dorsal striatum.…”
Section: Characterization Of Corticostriatal Bdnf Neuronssupporting
confidence: 58%
“…In the OFC, BDNF is critical for goal-directed decision making and in selecting actions based on their consequences (Gourley et al, 2013). In the motor cortex, BDNF contributes to motor learning (Andreska et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There have been several previous attempts to quantify neurophysiological markers of motor learning and performance (Baetu et al, 2015;Andreska et al, 2020;Herszage et al, 2020). Such attempts have included resting-state electroencephalography (EEG) activity, which has been shown to pre-dict visuomotor performance with the rotary pursuit task (Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the Sox6 gene contains a synaptic activity-responsive element (SARE), a regulatory enhancer element originally discovered in the immediate early gene Arc ( Kawashima et al, 2009 ) that predicts transcriptional changes in response to neuronal activation ( Rodriguez-Tornos et al, 2013 ; Pulimood et al, 2017 ). Therefore, to test the hypothesis that Sox6 expression in cortical Pvalb + cells can be modulated by increased network activity, we moved to the M1, a cortical region engaged during motor learning ( Kleim et al, 1996 , 1998 ; Beloozerova et al, 2003 ; Costa et al, 2004 ; Hosp et al, 2013 ; Cao et al, 2015 ; Andreska et al, 2020 ). We used the accelerating rotarod task as a means of enforcing locomotor activity and thus triggering increased neuronal firing in M1 ( Costa et al, 2004 ), which augments expression of activity-regulated genes in both pyramidal neurons ( Cao et al, 2015 ; Hirata et al, 2016 ) and in Pvalb + cells ( Arango-Lievano et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%